Exploring Classroom Discipline Strategies and Cultural Dynamics: Lessons from the Japanese Education System - Badawi, Habib (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
This academic study examines classroom discipline strategies and cultural dynamics within the Japanese education system. It focuses on their effects on classroom management and cross-cultural education. The study aims to provide valuable lessons from the Japanese approach to classroom discipline, student engagement, and the influence of national factors on student-teacher relationships and communication. The main objective of the study is to highlight the fundamental rules of Japanese classrooms, emphasizing respect, hierarchy, and authority. It examines how these values shape the overall discipline and approach adopted by Japanese teachers. This will help in providing a framework for understanding unique classroom management practices in Japan. This study provides valuable insights into classroom management strategies in Japan and their relevance to cross-disciplinary education. By understanding Japanese classroom cultural dynamics and discipline strategies, educators and policymakers can gain a broader perspective. They can also adapt effective practices to create inclusive and engaging learning environments. The study also suggests avenues for future research, encouraging further exploration of cultural dynamics and their implications for education systems worldwide.